2005
DOI: 10.1165/rcmb.2004-0293oc
|View full text |Cite
|
Sign up to set email alerts
|

Defective Surfactant Secretion in a Mouse Model of Hermansky-Pudlak Syndrome

Abstract: The lamellar body of alveolar epithelial type II cells is a lysosomerelated, intracellular storage organelle for newly synthesized and recycled surfactant components. As such, this organelle interfaces with both the secretory and endosomal pathways within the type II cell. Newly synthesized hydrophobic surfactant proteins, surfactant protein (SP)-B and -C, traffic to (and, in the case of SP-C, complete post-translational processing in) the lamellar body (1), whereas the hydrophilic surfactant protein, SP-A, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 50 publications
(52 reference statements)
2
63
1
Order By: Relevance
“…Figure 3B). This is in contrast to our prior report, in which we did not find differences in large and small aggregate total SP-D levels in comparing WT and EPPE animals at 16 weeks of age (7). In the present study we used an antibody with higher specificity for mouse (and human) SP-D (as described in the online supplement), and analyzed equal volumes of unfractionated BAL for total SP-D (4, 7).…”
Section: Resultscontrasting
confidence: 77%
See 1 more Smart Citation
“…Figure 3B). This is in contrast to our prior report, in which we did not find differences in large and small aggregate total SP-D levels in comparing WT and EPPE animals at 16 weeks of age (7). In the present study we used an antibody with higher specificity for mouse (and human) SP-D (as described in the online supplement), and analyzed equal volumes of unfractionated BAL for total SP-D (4, 7).…”
Section: Resultscontrasting
confidence: 77%
“…In our prior study we normalized total SP-D immunoblotting data to BAL total protein and total phospholipid. This normalization presented a problem in retrospect because of elevated total protein and reduced total phospholipid in BAL from EPPE mice, as we and others have reported (4,7), leading us to conclude that total SP-D was not altered in the EPPE mice. In the present study we instead reported total SP-D in equivalent volumes of BAL from EPPE mice ( Figure 3) and patients with HPS1 ( Figure 5), and found dramatic differences that progressed with age in EPPE mice, and with disease severity in patients with HPS1.…”
Section: Discussionmentioning
confidence: 70%
“…Mouse models of the human disease Hermansky-Pudlak syndrome also demonstrate altered surfactant homeostasis. However, unlike Gpr116 Dexon17 , Sftpd 2/2 , and Csf2 2/2 mice, mice with mutations in HermanskyPudlak syndrome-associated genes exhibit decreased alveolar pools of surfactant phospholipids and increased tissue phospholipid levels due to defects in surfactant trafficking and decreased secretion in type II cells (42)(43)(44). Taken together, our data support the hypothesis that GPR116 controls alveolar surfactant pool sizes by negatively regulating surfactant secretion from type II cells.…”
Section: Surfactant In Gpr116supporting
confidence: 76%
“…It is thus likely that the BLOC-1-dependent pathway that we have defined is ubiquitous in mammals, but it has been exploited by specialized cell types for delivery of specific cargo to LROs, such as melanosomes, platelet dense granules, and lung lamellar bodies, and/or to synaptic vesicles (McGarry et al, 2002;Talbot et al, 2004;Bray et al, 2005;Guttentag et al, 2005). Our data suggest that at least one critical cargo protein is targeted from early endosomes to each of these organelles in a BLOC-1-dependent manner.…”
Section: Discussionmentioning
confidence: 75%